2021
DOI: 10.1186/s12935-021-02163-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNA methylation N6-methyladenosine regulators on malignant progression and prognosis of melanoma

Abstract: Background Melanoma is an extremely aggressive type of skin cancer and experiencing a expeditiously rising mortality in a current year. Exploring new potential prognostic biomarkers and therapeutic targets of melanoma are urgently needed. The ambition of this research was to identify genetic markers and assess prognostic performance of N6-methyladenosine (m6A) regulators in melanoma. Methods Gene expression data and corresponding clinical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Liu et al. reported that METTL16 was associated with poor prognosis of patients with melanoma [ 53 ]. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. reported that METTL16 was associated with poor prognosis of patients with melanoma [ 53 ]. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP3 might be a pan-cancer oncogene, as its overexpression is associated with poor patient survival in various cancers, including kidney renal clear cell carcinoma, kidney renal papillary cell carcinoma, brain lower-grade glioma, and more [ 98 ]. Moreover, IGF2BP3 is upregulated and its high expression conveys tumor progression and worse prognosis in patients with lung adenocarcinoma [ 99 ], esophageal cancer [ 100 ], gastric cancer [ 63 ], pancreatic adenocarcinoma [ 101 ], papillary renal cell carcinoma [ 102 ], colon cancer [ 56 ], clear cell renal cell carcinoma [ 61 ], bladder cancer [ 103 ], prostate cancer [ 104 ], nasopharyngeal carcinoma [ 64 ], laryngeal squamous cell cancer [ 60 ], melanoma [ 105 ], glioma [ 106 ], acute myelocytic leukemia [ 65 ], among others. IGF2BP1 has been identified as an unfavorable prognostic indicator in tumors such as lung adenocarcinoma [ 107 ], endometrial cancer [ 42 ], gastric cancer [ 108 ], hepatocellular carcinoma, and serous ovarian cancer [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that IGF2BP3 promoted proliferation and migration of melanoma cells in vitro. The expression of IGF2BP3 was positively correlated with lymph node metastasis and immune cells infiltrating [ 42 ]. These results provided potential targets of novel drugs for melanoma.…”
Section: Roles Of M 6 a Methylation In Skin Tumorsmentioning
confidence: 99%